Implementasi Time Management Dalam Mereduksi Stres Kerja Karyawan PT. Perkebunan Sawit XYZ - Diny Atrizka; Ikbar Pratama; Agung Suharyanto (Pelita Masyarakat, 2022)
Stress is a condition that affects emotions, thought processes and individual conditions. When an employee faces stressed, it will be able to interfere with the individual's ability to deal with the surrounding environment and it’s work. There are a number of working conditions that often cause stress for employees, including excessive workload, pressure or time pressure, poor quality of supervision, unsafe climate, insufficient feedback on work performance, ambiguity of roles, frustration, conflict b between groups, interpersonal conflict, differences between company and employee values. Job stress cannot be ignored because it can interfere health, but this can be prevented or anticipated through time management training to reduce stress. Time management is a skill related to all the efforts and actions of an employee that are carried out in a well planned, so that the individual can use time effectively and efficiently. After training conducted, the results are able to reduce stress of PT. XYZ Palm Plantation’s employee, which is described in the evaluation response paper.